Development of a Binary Digestion System for Extraction Microplastics in Fish and Detection Method by Optical Photothermal Infrared - Yan, Feifei; Wang, Xiaochen; Sun, Haoran; Zhu, Zixian; Sun, Weihong; Shi, Xiangli; Zhang, Jinpeng; Zhang, Ling; Wang, Xiaofeng; Liu, Mengyang; Cai, Minggang; Zhang, Ying (Frontiers in Marine Science, 2022)
Accumulating evidence indicates that aquatic organisms ingest microplastics (MPs), which may be a threat to essentially the entire global ecosystem. In current detection methods, even in cutting-edge nanoplastic technology, a major challenge for detecting microplastics (MPs) in aquatic organisms is removing complex biological matrices, such as fat. Herein we report combining HNO3 and H2O2 to form a binary digestive reagent system to determine MPs in biological tissue. With insights obtained from a Gaussian model, the adding manners of two reagents were discussed. Thus, in the final protocol, we mixed MPs and tissue with 20 mL of 30% (v/v) aqueous H2O2, 10 mL 0.5 M NaOH,1 mL 5 mM Fe2+, and 40 mL 11.5% (v/v) aqueous HNO3, in sequence at different time intervals. What’s more, sodium dodecyl sulfate (SDS) and ultrasound—alone or together—were explored to solve the problem of removing fat residues and thus membrane blockage during filtration. In this paper, we used the O-PTIR microscope to verify the feasibility of the protocol. Compared with traditional detection methods, the O-PTIR spectroscopy can significantly improve the lateral resolution, down to sub and super-micrometer, and the ability to quickly obtain high spatial resolution far-field non-contact infrared spectra, which provide a novel method for qualitative analysis of MPs. In field applications, in our attempt, the fixed wavenumber image by O-PTIR can realize sub and super-micrometer MPs in situ, far-field measurements. The present method is highly efficient, and facilitates the identification of plastic particles.